1989
DOI: 10.1161/01.res.65.3.671
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonate metabolism in cultured fibroblasts derived from normal and infarcted canine heart.

Abstract: Metabolites of arachidonic acid (eicosanoids) may have an important role in the healing process after myocardial infarction. We examined the ability of cardiac fibroblasts from normal and from healing infarcted ventricle to metabolize arachidonate. We induced myocardial infarction in dogs and then allowed them to recover for 1 week, at which time they were killed, and the heart was removed. Fibroblasts were harvested from normal and from the healing, infarcted areas of the left ventricle. The cells from each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…In patients with acute myocardial infarction who are not receiving a thrombolytic agent, PGI2 formation rose over the 48 hours after admission and gradually declined toward normal by day 5.5,14,40 This activity correlated closely with plasma CPK level, and striking increases occurred in patients with large myocardial infarctions, findings that suggest that the increase in PG12 biosynthesis derives from the heart.14,41 The cellular origin is uncertain, but it is probably vascular endothelium because isolated myocardial cells have no prostaglandin synthase activity and endothelial cells are the major source of PGI2 in myocardial tissue.42 Furthermore, injured myocytes release arachidonic acid,43 which may be metabolized by other cells to form prostaglandins including PGI2. 44 Although the number of patients was small, a similar increase in PGI2 was seen in patients who failed to reperfuse after t-PA administration. In contrast, the increase in PGI2 biosynthesis was blunted in patients who reperfused, and it did not correlate with plasma CPK.…”
Section: Resultsmentioning
confidence: 82%
“…In patients with acute myocardial infarction who are not receiving a thrombolytic agent, PGI2 formation rose over the 48 hours after admission and gradually declined toward normal by day 5.5,14,40 This activity correlated closely with plasma CPK level, and striking increases occurred in patients with large myocardial infarctions, findings that suggest that the increase in PG12 biosynthesis derives from the heart.14,41 The cellular origin is uncertain, but it is probably vascular endothelium because isolated myocardial cells have no prostaglandin synthase activity and endothelial cells are the major source of PGI2 in myocardial tissue.42 Furthermore, injured myocytes release arachidonic acid,43 which may be metabolized by other cells to form prostaglandins including PGI2. 44 Although the number of patients was small, a similar increase in PGI2 was seen in patients who failed to reperfuse after t-PA administration. In contrast, the increase in PGI2 biosynthesis was blunted in patients who reperfused, and it did not correlate with plasma CPK.…”
Section: Resultsmentioning
confidence: 82%
“…Although these results point to a possible role for PGs in the regulation of cardiac growth, other cardiovascular effects such as a reduction in blood viscosity (18) cannot be ruled out. Prostaglandin synthesis is also greater in cardiomyocytes (47), endothelial cells (48) and fibroblasts (49) subjected to hypoxia. The role of PGF 2␣ in hypoxia may be to aid recovery of injured myocytes by stimulating protein synthesis, as well as to stimulate growth of uninjured myocytes to restore a decrement in myocardial contractility.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, isolated canine cardiac fibroblast-like cells were found to have greater cyclooxygenase activity and PGE 2 production in the infarcted tissue compared with fibroblasts of the noninfarcted tissue. 9 Recently, Siragy et al 10 demonstrated that Agtr2Ϫ/Y mice, compared with wild-type (WT) mice, had higher basal levels of PGE 2 and lower prostaglandin F 2␣ (PGF 2␣ ) levels in renal interstitial fluid under basal or dietary sodium restriction. Given the appearance of PGs in inflammatory cells in healing wound, these observations suggest possible differences in the response of heart to infarction in AT 2 gene-deleted mice.…”
Section: See P 2167mentioning
confidence: 99%